Perspectives on historical syntax - Viti, Carlotta (Studies in language <Amsterdam> / Companion series, 2015)
Perspectives on Historical Syntax -- Editorial page -- Title page -- LCC data -- Table of contents -- Introduction -- Historical syntax -- 1. Historical syntax as an emerging field -- 2. Controversial problems of syntactic change and of syntactic reconstruction -- 2.1 Mechanisms of syntactic change -- 2.2 Feasibility of syntactic reconstruction -- 3. Relevance of the present volume for current historical syntax -- 3.1 An interdisciplinary approach -- 3.2 Syntactic change -- 3.3 Syntactic reconstruction -- 3.4 Historical syntax and corpus linguistics -- 3.5 Historical syntax and language contact -- 4. Summary -- References -- Syntactic change -- Manner deixis as source of grammatical markers in Indo-European languages -- 1. Introduction -- 2. Basic distinctions -- 2.1 Demonstratives -- 2.2 Additional distinctions in the content and in the deictic dimension -- 3. Methodology -- 4. The exophoric use: Loss and renewal -- 5. From exophoric to anaphoric and cataphoric use -- 6. From anaphora to connective -- 7. From cataphoric to quotative -- 8. From endophoric determiner to comparative marker -- 9. From quality deixis to relative clause marker -- 10. Summary and conclusions -- References -- Time for change -- 1. Real times in historical linguistics -- 1.1 Signals from the past, 1: Absolute dating -- 1.2 Signals from the past, 2: Relative dating -- 1.3 Why date at all? -- 1.4 Life expectancy of lexicon and grammar -- 1.4.1 Time-stability -- 1.4.2 Tempo of change -- 2. The tempo of grammaticalisation: From noun to adposition, within 16 generations -- 2.1 French -- 2.2 North Germanic: East and West -- 2.2.1 Continental Scandinavian -- 2.2.2 Insular Scandinavian -- 2.3 Pāli, Sinhalese and Maldivian -- 2.4 Elsewhere -- 2.5 What takes so much time? -- 2.5.1 Social diffusion -- 2.5.2 Composite change -- Acknowledgments -- References
Description based upon print version of record
Keywords: Electronic books; Aufsatzsammlung; Syntax; Historische Sprachwissenschaft; Historische Syntax